2002
DOI: 10.1139/x02-096
|View full text |Cite
|
Sign up to set email alerts
|

The dendroclimatic signal in Douglas-fir and ponderosa pine tree-ring chronologies from the southern Canadian Cordillera

Abstract: A network of 53 ring-width chronologies has been developed from low-elevation stands of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco, n = 40) and ponderosa pine (Pinus ponderosa Dougl. ex P. & C. Laws., n = 13) in the southern Canadian Cordillera. Relationships between the chronologies and monthly, seasonal, and annualized climatic parameters (precipitation, temperature, and Palmer Drought Severity Index (PDSI)) were investigated using correlation analyses. The results indicate that tree growth at the sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 26 publications
10
60
1
Order By: Relevance
“…We limited our analyses to seasonal and annual variables, as preliminary data analyses and other studies (e.g., Watson and Luckman 2002) have shown that integrations of climate over multiple months (i.e., seasons) are more important growth influences than variation at a monthly scale. Seasonal and annual climate variables were derived by averaging monthly values based on a priori knowledge of appropriate climate variables suitable for use in describing Douglas-fir climate-growth relationships (Watson and Luckman 2002;Littell et al 2008;Griesbauer and Green 2010) and preliminary data analyses. Growth was compared to climate variables from July prior to the growing season through October following the growing season, as climate in the preceding year can affect the current year's growth (Fritts 1976).…”
Section: Climate Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We limited our analyses to seasonal and annual variables, as preliminary data analyses and other studies (e.g., Watson and Luckman 2002) have shown that integrations of climate over multiple months (i.e., seasons) are more important growth influences than variation at a monthly scale. Seasonal and annual climate variables were derived by averaging monthly values based on a priori knowledge of appropriate climate variables suitable for use in describing Douglas-fir climate-growth relationships (Watson and Luckman 2002;Littell et al 2008;Griesbauer and Green 2010) and preliminary data analyses. Growth was compared to climate variables from July prior to the growing season through October following the growing season, as climate in the preceding year can affect the current year's growth (Fritts 1976).…”
Section: Climate Datamentioning
confidence: 99%
“…Previous studies have established a strong link between Douglas-fir radial growth and precipitation in BC (e.g., Watson and Luckman 2002;Griesbauer and Green 2010) and other regions (e.g., Littell et al 2008). What remains unclear is the nature of climate-growth relationships at the species' NRM (Griesbauer and Green 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Dendrochronological studies at broad spatial and temporal scales could provide useful information on the spatiotemporal variation of tree growth (Villalba and Veblen 1997;Watson and Luckman 2002;Tardif et al 2003). These studies are also essential to validate climate model simulations in climatesensitive regions such as the high-elevation Tibetan Plateau where existing instrumental climatic data have a low resolution over space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect of developing a long proxy record from tree rings is maintaining climatic signal at a regional scale . It seems that assessment of the regional climatic signal in mountain areas demands a wider network of treering chronologies because of a higher variety of growth conditions caused by topography (Watson and Luckman 2002). Furthermore, growth conditions in highlands might be amplified by the impact on tree-ring growth of glacier behavior, ice fields, avalanches, debris flows, landslides, etc.…”
Section: Introductionmentioning
confidence: 99%